Nonlinear Integral Equation of Inverse Scattering Problems of Wave Equation and Iteration (Journal of Computational Mathematics, 2021)
In this paper, we reduce the 1-D, 2-D and 3-D inverse scattering problems of the wave equation into the nonlinear integral equation. The iteration for solving the above integral equations has been considered.